2021
DOI: 10.1002/pei3.10064
|View full text |Cite
|
Sign up to set email alerts
|

Response of grassland net primary productivity to dry and wet climatic events in four grassland types in Inner Mongolia

Abstract: Increasing frequency and intensity of climate extremes have profound impacts on grassland biodiversity functioning and stability. Using Moderate Resolution Imaging Spectroradiometer (MODIS) net primary productivity (NPP) data and standardized precipitation evapotranspiration index, we assessed the response of NPP to growingseason and annual climate extremes and time-lag of climatic conditions across four grassland types (meadow steppe, typical steppe, steppe desert, and desert steppe) in Inner Mongolia, China … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 74 publications
(142 reference statements)
1
9
0
Order By: Relevance
“…Owing to the fragile ecological environment of these temperate grasslands, the study area is very sensitive to climate change ( Bao et al, 2019 ; Bai et al, 2021 ). Temperate desert grassland is mainly concentrated in the west of the study area, with annual mean temperature of 7.2°C and annual precipitation of 45–215 mm ( Hossain et al, 2021 ). Temperate steppe is the most widely distributed and representative of the various grassland types.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the fragile ecological environment of these temperate grasslands, the study area is very sensitive to climate change ( Bao et al, 2019 ; Bai et al, 2021 ). Temperate desert grassland is mainly concentrated in the west of the study area, with annual mean temperature of 7.2°C and annual precipitation of 45–215 mm ( Hossain et al, 2021 ). Temperate steppe is the most widely distributed and representative of the various grassland types.…”
Section: Methodsmentioning
confidence: 99%
“…Grassland ecosystems play a key role in regulating the carbon cycle and maintaining ecological balance ( Bengtsson et al, 2019 ; Hoover et al, 2022 ; Shen et al, 2022a , b ). Net primary productivity (NPP) is not only a crucial indicator of carbon sequestration ( Zhang et al, 2016 ; Hossain et al, 2021 ), but also a key reference for assessing grassland ecosystem function ( Seeber et al, 2022 ; Wang et al, 2022 ). Previous studies have shown that climate change has significant effects on grassland NPP ( Liu et al, 2021 ; Xiong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Orimoloye et al [ 35 ] stated that drought can be evaluated by analyzing green vegetation through Normalized Vegetation Water Index (NDWI), Soil Adjusted Total Vegetation Index (SATVI), Land Surface Temperature (LST), Normalized Difference Vegetation Index (NDVI), Normalized Drought Dryness Index (NDDI), Vegetation Condition Index (VCI) and Temperature Vegetation Dryness Index (TVDI). Furthermore, satellite-based remote sensing data provides an advanced way to understand the scenario of natural resource depletion [ 36 ], monitor ecosystem health [ 37 ], and predict the climate-induced changes in soil, water, and biodiversity [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meadow vegetation is highly responsive to environmental factors [Rabotnov, 1974]; therefore, it can be used as adequate model objects for analysis of various impacts, which is fully exploited by foreign scientists. In particular, experiments are underway to study the impact of extreme climatic factors on vegetation growth [Zhang L. et al, 2021;Hossain et al, 2021] to maintain stable functioning of plant ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the studies of meadows have involved the analysis of the impact of climatic and hydrological factors on biodiversity [Zelnik andCarni, 2013, Zhang L. et al, 2021;Hossain et al, 2021] and the net primary productivity of meadows to study the global carbon cycle [Moore et al, 2013;Zhang F. et al, 2017;Zhang B. et al, 2019;Quan et al, 2020].…”
Section: Introductionmentioning
confidence: 99%